UV/VIS spectral simulation of a symmetrical disazo direct dye by the Hartree-Fock approximation - Rădulescu-Grad Maria Elena; Funar-Timofei Simona; International Symposium on Analytical and Environmental Problems (26.) (2020) (Szeged) (2020)
A disazo direct dye having a symmetrical structure, derived from the 4,4'-diaminostilbene-2,2'- disulfonic acid was previously synthesized and applied to water-based acrylic resins, in coatings. The dye structure was previously experimentally analyzed using the UV/VIS spectroscopy and theoretical Density Functional Theory (DFT) calculations were employed to compare the calculated with the experimental UV/VIS wavelengths. In this paper the molecular dye structure was modeled using the MMFF94 force field and the Hartree-Fock (HF) approach. The UV/VIS spectrum of the minimum energy optimized structure was simulated using the Configuration Interaction Singles (CIS), the Time-Dependent (TD) and the Zerner's Intermediate Neglect of Differential Overlap (ZINDO) methods to evaluate the electronic excitation spectra. The ZINDO approach gave better maximum absorption calculated values compared to the CIS and TD methods, as previously noticed in case of using the DFT approach. A generally good agreement between the experimental and theoretical computed absorption maxima was noticed.